47 Babaker-sponsored students celebrate Eid at UMPSA - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 16 April 2024 - Syawal continued to be celebrated in the Aidilfitri Celebration Ceremony with international students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) at Banquet Hall, UMPSA Pekan recently.